(untitled) (Journal of Nepal Physical Society, 2020)
We present dust color temperature, Planck function and visual extinction distributions of a far infrared cavity FIC19+30 found to be located around post-AGB star namely AGB20+29 at the galactic plane. Minimum and maximum dust color temperature of the core region of the cavity was found to be (22.17±0.23) K and (22.41±0.29) K respectively with offset value 0.24 K which suggests that the cavity is isolated and stable. The product of dust color temperature and visual extinction was found to be in the order of 10-4 K mag. The distribution of Planck function along the extension (major diameter) and compression (minor diameter) was found to be non-uniform distribution. Specifically dust particles are oscillating in order to get dynamical equilibrium which may be the cause of grain temperature. It further suggests that the dust particles in the cavities might not be in the thermal equilibrium possibly due to pressure driven events of nearby AGB stars. There is continuous increase in flux density with increase in wavelength as in case of nebula which suggests that number density of dust particles increase according to the increase in wavelength and vice-versa.